Program Parenting SOS (Sekolah Orang Tua Santri) Di TK Ihya Assunnah Tasikmalaya - Faza Tsamrotul Apipah; Rika Nurhayati; Zahira Auladina Solihah; Gina Khaerunnisa; Purwati Purwati; Heri Yusuf Muslihin (Universitas PGRI Semarang, 2023)
AbstractIn an effort to stimulate the growth and development of early childhood, of course, its not only the task of educators in school institutions, but the importance of the involvement of parents and teachers in optimizing the growth and development of early childhood and aligning parenting styles in early childhood. The purpose of this study was to find out about the parenting program held at TK Ihya Assunnah Tasikmalaya. The research method used is a qualitative research method, describes the research results descriptively. Data collection techniques using the method of observation, interviews, and documentation. The results of this study are the parenting program held at Ihya Assunnah Kindergarten is SOS (Santri Parents School). The program is implemented through tiered training attended by parents and those involved in the childcare process. This program can be implemented through the stages of planning, implementation, evaluation, and follow-up. This parenting program, parents know more about and apply appropriate parenting patterns, how to stimulate children, and parents are more cooperative towards the programs held at Ihya Assunnah Kindergarten. With the existence of the SOS parenting program, it is hoped that it can increase parental awareness regarding the importance of parental involvement in early childhood education.Keywords: parenting programs; parent involvement; early childhoodAbstrakDalam upaya menstimulasi tumbuh kembang anak usia dini tentunya tidak hanya tugas pendidik di lembaga sekolah, tetapi pentingnya keterlibatan orang tua dan guru dalam mengoptimalkan tumbuh kembang anak usia dini dan menyelaraskan pola asuh pada anak usia dini. Tujuan penelitian ini untuk mengetahui lebih lanjut mengenai program parenting yang diselenggarakan di TK Ihya Assunnah Tasikmalaya. Metode penelitian yang digunakan adalah metode penelitian kualitatif, yaitu menjabarkan hasil penelitian secara deskriptif. Teknik pengumpulan data menggunakan metode observasi, wawancara, dan dokumentasi. Hasil penelitian ini yaitu program parenting yang diselenggarakan di TK Ihya Assunnah disebut dengan SOS atau Sekolah Orang Tua Santri. Program tersebut dilaksanakan melalui pelatihan berjenjang yang diikuti oleh orang tua maupun pihak yang terlibat dalam proses pengasuhan anak. Program ini dapat terlaksana melalui adanya tahapan perencanaan, pelaksanaan, evaluasi, dan tindak lanjut. Dengan adanya program parenting tersebut, orang tua lebih mengetahui dan menerapkan pola pengasuhan yang tepat, cara menstimulasi anak, serta orang tua lebih kooperatif terhadap program yang diselenggarakan di TK Ihya Assunnah. Dengan adanya program parenting SOS ini diharapkan dapat meningkatkan kesadaran orang tua mengenai pentingnya keterlibatan orang tua pada pendidikan anak usia dini.Kata kunci: Program Parenting; Keterlibatan Orang Tua; Anak Usia Dini.